An electrochemical sensor for forane - Northing, R (1989)
﻿ This thesis is concerned with the development and laboratory assessment of an electrochemical sensor for the detection and measurement of the volatile inhalation anaesthetic, forane. Investigations were therefore based on the heterogeneous and homogeneous reduction of this agent in non-aqueous electrolyte. Preliminary experiments at a mercury and other rotating disc electrodes (RDEs) revealed that the direct reduction of forane was not possible and therefore the use of an electron transfer mediator was examined. To this end, the radical anion of the polyaromatic compound, fluoranthene, (F), was investigated as a possible electro-reduction catalyst and the mediated reduction of the anaesthetic, via a catalytic process, demonstrated. Theory was presented for the calculation of chronoamperometric and steady state responses at the RDE resulting from one electron transfer and coupled (catalytic) homogeneous kinetic processes. The latter enabled a precise mechanism to be assigned to the F + forane process, while a comparison of the former theory with experimental chronoamperometric results was used, in conjunction with AC impedance studies, to investigate the adsorption of F at the mercury/acetonitrile interface. A polymer modified electrode, based on the polymer poly-(11-vinylfluoranthene) was demonstrated to be effective in the heterogeneous reduction of forane but displayed only a limited lifetime. Therefore, a Clark-type membrane electrode was constructed and the detection and measurement of forane, in the absence of oxygen, demonstrated using this device. However, the sluggish response of this sensor, together with interference problems from oxygen encouraged the development of a device which utilised a channel electrode (ChE) sensing approach. Theory was presented for the deduction of steady state currents at the ChE resulting from coupled catalytic kinetics and this was used to demonstrate that the same mechanism for the F + forane system operated at the ChE as the RDE. The conventional ChE was then modified by the incorporation of a membrane and this sensor, which was shown to operate successfully in the presence of high concentrations of oxygen and nitrous oxide, responded linearly to forane, while displaying an excellent response time of under ten seconds. The device should find application in clinical monitoring.